Culinary Spice Plants in Dietary Supplement Products and Tested in Clinical Trials - Saldanha, Leila G; Dwyer, Johanna T; Betz, Joseph M (Advances in nutrition (Bethesda, Md.), 2016)
Dried plant parts used as culinary spices (CSs) in food are permitted as dietary ingredients in dietary supplements (DSs) within certain constraints in the United States. We reviewed the amounts, forms, and nutritional support (structure/function) claims of DSs that contain CS plants listed in the Dietary Supplement Label Database (DSLD) and compared this label information with trial doses and health endpoints for CS plants that were the subject of clinical trials listed in clinicaltrials.gov. According to the DSLD, the CS plants occurring most frequently in DSs were cayenne, cinnamon, garlic, ginger, pepper, rosemary, and turmeric. Identifying the botanical species, categorizing the forms used, and determining the amounts from the information provided on DS labels was challenging. CS plants were typically added as a component of a blend, as the powered biomass, dried extracts, and isolated phytochemicals. The amounts added were declared on about 55% of the labels, rendering it difficult to determine the amount of the CS plant used in many DSs. Clinicaltrials.gov provided little information about the composition of test articles in the intervention studies. When plant names were listed on DS labels and in clinical trials, generally the common name and not the Latin binomial name was given. In order to arrive at exposure estimates and enable researchers to reproduce clinical trials, the Latin binomial name, form, and amount of the CS plant used in DSs and tested in clinical trials must be specified.